Analysis of financial knowledge and financial attitude on locus of control and financial management behavior - Anis Dwiastanti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
This study aims to examine the direct and indirect influence of financial knowledge and financial attitude on locus of control and financial management behavior. The subject of this study used the students of Faculty of Economics and Business at Kanjuruhan University Malang in academic year of 2014 and 2015 as the sample determined by proportional random sampling. Data analysis technique is done by using path analysis. The results showed that financial knowledge has no influence on the locus of control or the financial management behavior. While the financial attitude has a significant effect on the locus of control and financial management behavior. This study also found a significant influence between locus of control with financial management behavior of students of Faculty of Economics and Business at Kanjuruhan University Malang